Stakeholder Perspectives and Business Risk Perception - Schwarzkopf, David L. (Journal of business ethics, 2006)
Stakeholder theory calls for decision makers to balance stakeholder interests, but before this can happen, management must understand how other parties view its decisions. Effective stakeholder dialogues convened to reach this understanding require management to appreciate how others perceive the risks posed by their decision. Although understanding others’ risk perception is crucial for effective communications, we do not have a clear idea of how viewing a situation from multiple stakeholder perspectives affects risk perception. Based on a technique derived from risk perception studies of health and environmental issues, an experiment with 224 business students examined how an individual’s risk perception can account for both managerial and customer perspectives. Factors described as customer participation, extent of the effect, and management input, together with the respondent’s self-assessed understanding of the decision process, help categorize overall risk perceptions and are shown to be associated with behaviors based on the decision’s riskiness. Discussion includes implications for designs of business communications, including their content and transparency, and for understanding the audience for these communications.